2023
DOI: 10.1113/jp285203
|View full text |Cite
|
Sign up to set email alerts
|

Loss of compensation afforded by accessory muscles of breathing leads to respiratory system compromise in the mdx mouse model of Duchenne muscular dystrophy

Ken D. O'Halloran,
Michael N. Maxwell,
Anthony L. Marullo
et al.

Abstract: Despite profound diaphragm weakness, peak inspiratory pressure‐generating capacity is preserved in young mdx mice revealing adequate compensation by extra‐diaphragmatic muscles of breathing in early dystrophic disease. We hypothesised that loss of compensation gives rise to respiratory system compromise in advanced dystrophic disease. Studies were performed in male wild‐type (n = 196) and dystrophin‐deficient mdx mice (n = 188) at 1, 4, 8, 12 and 16 months of age. In anaesthetised mice, inspiratory pressure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…Reduced respiratory frequency and tidal volume in mdx mice at 3 and 6 months (Huang et al., 2011) has also been reported, while at 7 months a reduction in respiratory frequency and minute ventilation compared to wild‐type has been demonstrated (Markham et al., 2015). Moreover, mdx mice show blunted ventilatory responses to hypercapnia (Gayraud et al., 2007) and hyperoxia and hypoxia at 8 weeks of age (Burns et al., 2017, 2018), although these changes maybe heterogeneous in their expression, as the same research group has reported no change in basal breathing or ventilatory responses to hypercapnic hypoxia in mdx mice over a considerable portion of the natural history of the disease (Burns et al., 2019; O'Halloran et al., 2023). In the golden retriever canine model of DMD, ventilatory insufficiency is also evident (Mead et al., 2014).…”
Section: The Respiratory System: An Integrated System Under Exquisite...mentioning
confidence: 99%
See 4 more Smart Citations
“…Reduced respiratory frequency and tidal volume in mdx mice at 3 and 6 months (Huang et al., 2011) has also been reported, while at 7 months a reduction in respiratory frequency and minute ventilation compared to wild‐type has been demonstrated (Markham et al., 2015). Moreover, mdx mice show blunted ventilatory responses to hypercapnia (Gayraud et al., 2007) and hyperoxia and hypoxia at 8 weeks of age (Burns et al., 2017, 2018), although these changes maybe heterogeneous in their expression, as the same research group has reported no change in basal breathing or ventilatory responses to hypercapnic hypoxia in mdx mice over a considerable portion of the natural history of the disease (Burns et al., 2019; O'Halloran et al., 2023). In the golden retriever canine model of DMD, ventilatory insufficiency is also evident (Mead et al., 2014).…”
Section: The Respiratory System: An Integrated System Under Exquisite...mentioning
confidence: 99%
“…Respiratory control in the mdx model of DMD has been comprehensively studied by our group (Burns et al., 2017, 2019; O'Halloran et al., 2023). Despite profound diaphragm weakness and decreased diaphragm electromyogram (EMG) activity, peak‐inspiratory pressure generating capacity is preserved for up to 12 months of age revealing that compensatory mechanisms offset the substantive dysfunction of the obligatory muscles of breathing in mdx mice.…”
Section: The Respiratory System: An Integrated System Under Exquisite...mentioning
confidence: 99%
See 3 more Smart Citations